Obstetric nurses’ attitudes to caring for couples with pregnancy loss - Ratola, Adriana; Martins, Patrícia; Coutinho, Emília (Millenium - Journal of Education, Technologies, and Health, 2025)
Introduction: Pregnancy loss is a traumatic event that affects many couples, who often report a lack of social and emotional support and need professional support, particularly from obstetric nurses. Objective: To understand the attitudes of obstetric nurses when caring for couples with pregnancy loss. Methods: A qualitative, phenomenological-hermeneutic study, based on Max Van Manen's presuppositions, approved by the Ethics Committee. Using snowball sampling, 14 obstetric nurses with experience in the field were selected for semi-structured interviews. The data collected was analyzed phenomenologically using MAXQDA 24 software. Results: The analysis of the testimonies of the 14 Obstetric Nurses allowed us to uncover the “Attitudes of the Obstetric Nurse at the time the couple receives the news of gestational loss”, where the following subcategories emerged: “Support unconditionally”, “Give space”, “Give the couple time to internalize the news”, “Use touch”, “Promote comfort”. None of the nurses had specific training in caring for couples with pregnancy loss. Among those who reported having some training, they reported “Content taught in the specialty”, “Participating in seminars”, “Having self-training”, “In service”, “Participation in Congresses, where the topic arises”. Among the most common emotions experienced were frustration, helplessness and feelings of inadequacy in being able to manage adequately in these situations. Conclusion: The evidence from the research suggests an emerging need for improvements in caring for couples with pregnancy loss at the developmental level of obstetric nurses, i.e. that they should be given specific training in the area so that they can care for couples with pregnancy loss more effectively and according to the needs of each couple, taking into account their uniqueness.